Antioxidant Effects of Amino Acids-Capped Silver Nanoprisms Against Cadmium-Induced Toxicity: Modified Silver Nanoprisms with Enhanced Potential - Ditta, Sarwar Allah; Yaqub, Atif; Haider, Arslan; Tanvir, Fouzia; Rashid, Muhammad (Iranian Journal of Pharmaceutical Sciences, 2022)
The surface functionality of nanomaterials (NMs) with suitable biomolecules may enhance their biocompatibility and make them more effective for biological applications. Furthermore, the functionalization of various materials with biomolecules would also yield more secure and biocompatible nanomaterials for different applications. The present research was designed to evaluate the amino acids-based surface functionality of silver nanoprisms (AgNPrs). Silver nanoprisms were prepared by chemical method and further capped with amino acids such as L-cystine (Cys), L-glycine (Gly), and L-tyrosine (Tyr). Characterization of the newly-synthesized NMs was performed by using various techniques. Prepared nanomaterials (NMs) were assessed for their in vitro antioxidant activity using diphenylpicrylhydrazyl (DPPH), ferric reducing power (FRP), and hydrogen peroxide (HP) scavenging assays. In vivo, the antioxidant potential of the same was evaluated in the cadmium-intoxicated Mus musculus model. Tyr-AgNPrs (p < 0.05), Cys-AgNPrs (p < 0.05), and Gly-AgNPrs (p > 0.05) showed enhanced DPPH scavenging activity. Whereas the Cys-AgNPrs displayed enhanced FRP activity and Tyr-AgNPrs displayed enhanced HP scavenging activity. The AgNPrs and cadmium-exposed mice displayed a decreased (p<0.05) catalase (CAT) activity in G2 and G3, whereas it increased in G4. The superoxide dismutase (SOD) activity was decreased in the G2 (p < 0.05) and G5 (p > 0.05) groups, whereas it increased in the G3 (p < 0.05), G4, and G6 groups of mice. The G2 showed a slightly decreased glutathione-s-transferase (GST) activity (p > 0.05). The levels of reduced glutathione (p<0.05) and metallothioneins (p>0.05) were elevated in the cadmium-intoxicated group. The results revealed that the cystine-AgNPrs and tyrosine-AgNPrs demonstrated higher antioxidant potential in comparison to other treatments. It is concluded that biomolecule-conjugated AgNPrs can work efficiently with more biocompatibility for various nanotechnological and biomedical applications.